Management of severe traumatic brain injury and acute respiratory distress syndrome using pumped extracorporeal carbon dioxide removal device. (February 2017) - Martindale, Tim; McGlone, Phillip; Chambers, Robert; Fennell, Jon
The effects of a high carbon dioxide on cerebral perfusion and intracranial pressure are well known. We report the case of a man who presented after with a severe traumatic brain injury including intracranial and extradural haemorrhage. Neuroprotective ventilation was impossible without supramaximal tidal volumes due to a combination of chest trauma and severe bronchospasm. A pump driven Novalung iLA active® system was inserted to achieve both ARDSnet ventilation and a lowering of intracranial pressure. To our knowledge, this is the first time this system has been used to this effect. The patient went on to make a good recovery.